Thrombotic Microangiophatic in the ICU, postpartum hemolytic uremic syndrome: case report - Zulma Urbina; Rayza Soledad; Juan Pablo Córdoba (Asociación Colombiana de Nefrología e Hipertensión Arterial, 2016)
Underlying injures produced by Hemolytic Uremic Syndrome, a clinical entity defined by the triad, inclu-de:  non-immune hemolytic anemia, thrombocytopenia, and organ involvement which are measured by the Trombotic Systemic Microangiopathy (TSM)  process. The atypical HUS (HUSa) is a subtype of HUS in which the phenomena of TSM are the result of the lack of regulation in alternative pathway of complements on cell surfaces, secondary to a genetic cause. The key role played by the deregulation of the complement system on the damaged endothelial layer in patients with HUSa has been established;   this system measures by multiple mutations and polymorphisms in the genes that encode certain regulatory proteins of the add-in has been established. Taking into account the great complement activity of physiological way during ges-tation, each day more cases of HUSa related to pregnancy, are described.  There is a monoclonal antibody, Eculizumab, which inhibits the terminal complement fraction (C5). Eculizumab blocks the formation of the attack complex of the membrane, with significant long-term improvement in morbidity and mortality asso-ciated with this disease, promoting long-term recovery of renal function and with a significant reduction in the need for dialysis or plasma therapy.A case of 17 year in puerperium, who developed icteric syndrome considered as HELLP syndrome, whose atypical evolution made us think about alternative diagnosis of thrombotic microangiopathy in pregnant woman HUSa type. Discard diagnosis between sepsis, HELLP syndrome and disseminated intravascular coagulation was made.  ADAMST13 measurement was taken, whose standard value allowed us to make the differential diagnosis with a Thrombotic Thrombocytopenic Purpura (TTP). In this way, we were able to achieve the clinical diagnosis of HUSa and begin treatment.